Perception of Multiple-Choice Questions: Its Challenges and Implication among Grade 12 Senior High Students of Mindanao State University-Sulu - Amil, Salha U. (Indonesian Community Empowerment Journal, 2022)
This study aimed to investigate the perception of multiple choice questions (MCQ) among grade 12 senior high students of Mindanao State University-Sulu. The descriptive survey method was used in this study. Random sampling was used to select 100 students, 50 from the GAS strand and 50 from STEM strand Grade 12 Senior high school students. The researcher prepared a survey questionnaire to obtain the necessary data. It was revealed that MCQ is challenging foremost due to the need to answer critically under time pressure. Consequently, they need to manage their time in order to answer every subject. The challenge of MCQ also lies in the difficulty of the subject. Also, the result revealed the implications of MCQ tends to urge students to answer each subject at a limited time pressure students that they experience test anxiety. Meanwhile, there is a need to look into the level of difficulty of the subject matter, which requires students' rigorous preparation before the exam. More so, MCQ develops students' analysis on problem-solving which provides them with a real-time experience of taking major exams and develops time management in studying and strategies in answering as it encourages them to answer with persistence and resilience.